Kinematics Research and Simulation Analysis of Parallel Mechanism Embossing Machine - Zhanxian Li; Jianli Xu; Jinfeng Huang (Jixie chuandong)
In order to solve some problems of embossing machine on the market today， a new parallel mechanism embossing machine with reasonable structure and simple control is presented. The overall structural scheme and outstanding features of the embossing machine are introduced， and the feasibility and practicality of this robot are discussed. The establishment of the mechanism composition and mechanism model of this parallel mechanism embossing machine is introduced. The kinematics mathematical model of the parallel mechanism embossing machine is established and the analytical form of the kinematics forward and inverse solutions is deduced to obtain its position， velocity and acceleration. Through the Adams software， the motion of the mechanism is analyzed， and the motion rule graph of the input and output components of the mechanism is obtained， and the motion law is analyzed to grasp its motion characteristics. The result of the kinematics study of the parallel mechanism embossing machine can provide reference for further research and optimization of the mechanism.